The United Nations, peace and security from collective security to the responsibility to protect - Thakur, Ramesh Chandra 1948-; Cambridge Books Online (Online service). (Cambridge New York Cambridge University Press, 2017)
"Ending humanitarian atrocities has become as important for the United Nations as preventing interstate war. This book examines the transformation of UN operations, analysing its changing role and structure. Ramesh Thakur asks why, when and how force may be used, and argues that the growing gulf between legality and legitimacy is evidence of an eroded sense of international community. He considers the tension between the United States, with its capacity to use force and project power, and the United Nations, as the centre of the international law enforcement system. He asserts the central importance of the rule of law and a rules-based order focused on the United Nations as the foundation of a civilised system of international relations. This book will be of interest to students of the United Nations and international organisations in politics, law and international relations departments, as well as policymakers in governmental and non-governmental international organisations"--Provided by publisher.
Machine generated contents note: 1. Pacific settlement, collective security and international peacekeeping; 2. Peace operations and the UN-US relationship; 3. Human security and human rights; 4. International criminal justice; 5. International sanctions; 6. The nuclear threat; 7. International terrorism; 8. Kosovo 1999 and Iraq 2003 as unilateral interventions; 9. Afghanistan, Libya and Syria: UN-authorised interventions and non-intervention; 10. From humanitarian intervention to R2P: cosmetic or consequential?; 11. The development and evolution of R2P as international policy; 12. Reforming the United Nations; 13. The political role of the United Nations Secretary-General.
Includes bibliographical references and index.
Keywords: United Nations; United Nations -- Peacekeeping forces; United Nations -- United States; Security, International; Pacific settlement of international disputes; Responsibility to protect (International law); Electronic books